Estimating an almost ideal demand system model of livestock and poultry across three time periods in the Philippines - Apolinares, Rennel John Vincent C.
Estimating demand especially on agricultural commodities has been an interest for many economists. Demand estimation can determine consumer responsiveness to changes in certain factors. This study is conducted to determine the demand of specific kind of livestock and poultry, which is pork, beef, and chicken in the Philippines using an aggregated cross-sectional data from the Bureau of Agricultural Statistics (BAS) using an dynamic modelling approach, which is the Almost Ideal Demand System (AIDS) of Deaton and Muellbeuer (1980). In a more specific term, this study aims to provide a comprehensive analysis on the responsiveness of the meat commodities to changes in their prices , price of substitute and the income level of the populace and the movement of these changes across three time-periods. Moreover, the study also determines the market potentiality of the meat commodities. Using the AIDS model and its specifications, the elasticities of pork, beef and chicken in their prices, prices of the substitute and income were determined. It was found out that the pork is a necessity good. Furthermore, the market potential of pork is high compared to chicken and beef. Chicken on one hand, have grown to become a normal good and has growing market potentiality. Lastly, beef with its high level of retail prices, are perceived by Filipinos as a luxury commodity as projected by its very elastic nature. Moreover, its market potential has decreased over time. Pork and chicken was determined to be competing meat commodities and beef on one hand complements the two.